2017
DOI: 10.1016/j.ebiom.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertrophic Effects of Small Molecules that Maintain Mitochondrial ATP Levels Under Hypoxia

Abstract: Since impaired mitochondrial ATP production in cardiomyocytes is thought to lead to heart failure, a drug that protects mitochondria and improves ATP production under disease conditions would be an attractive treatment option. In this study, we identified small-molecule drugs, including the anti-parasitic agent, ivermectin, that maintain mitochondrial ATP levels under hypoxia in cardiomyocytes. Mechanistically, transcriptomic analysis and gene silencing experiments revealed that ivermectin increased mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…This prevents pathological hypertrophy and improves cardiac function. Nagai H et al 2017 [ 67 ] *available as preprint; Clinical trials of IVM on COVID-19 available on https://clinicaltrials.gov[ 7 ]; Ivermectin for COVID-19: real-time meta-analysis available on https://ivmmeta.com [ 8 ]
Fig. 1 A schematic of the key cellular and biomolecular interactions between Ivermectin, host cell, and SARS-CoV-2 in COVID-19 pathogenesis and prevention of complications.
…”
Section: Introductionmentioning
confidence: 99%
“…This prevents pathological hypertrophy and improves cardiac function. Nagai H et al 2017 [ 67 ] *available as preprint; Clinical trials of IVM on COVID-19 available on https://clinicaltrials.gov[ 7 ]; Ivermectin for COVID-19: real-time meta-analysis available on https://ivmmeta.com [ 8 ]
Fig. 1 A schematic of the key cellular and biomolecular interactions between Ivermectin, host cell, and SARS-CoV-2 in COVID-19 pathogenesis and prevention of complications.
…”
Section: Introductionmentioning
confidence: 99%
“…Samples in different dilutions and positive control (40-mM propranolol hydrochloride, VWR, Radnor, Pennsylvania, USA) and EarlyTox Cardiotoxicity Kit (Molecular Devices, San-Jose, California, USA) were added for 2 hours at 37 C according to the manufacturer's protocol. 30 Spontaneous calcium transients were captured in single cells at Ex 470 nm/Em 500-530 nm for 30 seconds using a Nikon high content screening system (Nikon CEE GmbH) prior and after the addition of samples and positive control. After subtraction of the background, the number of spikes (only those with amplitudes >30 AFU) per 30 seconds was manually counted before and after the treatment.…”
Section: Cell Line Characterization In Vitro Exposure Technique and mentioning
confidence: 99%
“…A recent study showed that hypoxic activation of HIF1α may occur due to mitochondrial dysfunction in response to increased intracellular Ca 2+ (ref. 64 ). Notably, similar to altered cardiomyocytes, Ca 2+ cycling was observed in the HIP rats 23 and mitochondrial disarrangement was observed in control RVCMs incubated with exogenous aggregated human amylin 24 .…”
Section: Resultsmentioning
confidence: 99%